Jakarta’s Urban Green Spaces as Butterfly Habitats and Its Implications for Climate Mitigation - Maharani, Andi Nazwa Aulia (BIODIVERS - BIOTROP Science Magazine, 2026)
Jakarta’s urban green spaces are more than city parks. They are small ecosystems alive with pollinators that keep urban nature functioning. To understand how vegetation and human activity influence butterfly diversity, this study surveyed five parks across the city using standardized observation methods, namely the Pollard Walk and Point Count. A total of 157 butterflies representing 22 species were recorded, with Eurema sp. appearing most frequently. Parks with lush, layered vegetation like Penjaringan Urban Forest Park hosted the most species, while heavily urbanized areas had fewer. The findings reveal that preserving diverse plants and reducing disturbance can make cities more resilient to climate change, one butterfly at a time.